(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
Criticizing linguistic idealism, Merleau-Ponty conceives the linguistic domaine through the prism of speech. The paper analyses the way in which Merleau-Ponty, in his courses concerning literature in the first half of the fifties, raises the issue of the emergence of ideality through the linguistic act, and what he proposes, in dialogue with Paul Valéry, to settle it.